Inuk yuwi ta = let's play with the crab - the semiotic relationship of early Mesoamerican, lower Central and South American cultures with crabs (Decapoda: Brachyura) - Jiménez, Guillermo V. (2025)
Introduction: The millenary tradition of the Bribri and Cabécar culture called Ak kuk (= pull of the rock) and/or Inuk yuwi ta (= let's play with the crab) consists of pulling a stone from one place to another collectively. For the Bribris it is the most important tradition and festivity. The instrument with the tied stone that they use for this task is graphically related to one of the most present and studied symbols in the iconography in Mesoamerica: the crossed bands. Objective: To analyze, from an American perspective, the role of the crab (Decapoda: Brachyura) in early American cultures, in their cultural concepts up to the present day. Methods: The human-crab relationship in Mesoamerica, lower Central and South America was studied in symbolism, cosmovision, cultural representations and iconography, ethnohistoric documentation, oral literature, and interviews. Results: The present study demonstrates a close link to the present day with crabs, since they combined the morphology of crabs and humans and other animals to create biomorphic cultural representations, utilizing pareidolia as a creative resource to sophisticate their iconographic language, incorporating the biology, morphology and structural geometry of the crab as a positional and conceptual grid. Conclusions: This study demonstrates the importance that brachyuran crabs had and still have in the first cultures of The Americas, the relation with crossed bands, highlight the relevance of the knowledge regarding the current culture of the Bribris and Cabécares deposited in the tradition Inuk yuwi ta (= let’s play with the crab), and the relation of this tradition with the collective, with the stone and with the water. This contribution allows an approach to the way in which these decapods were reflected in the artistic, ludic manifestations as well as in the cosmovision of the studied cultures.